Leverage and firm performance : the case of manufacturing firms in Iceland - Benedikt Svavarsson 1997- (2022)
In this study we analyze the leverage and performance relationship within 2,055 Icelandic manufacturing firms from a dataset granted by Creditinfo hf. that includes financial statements that range between the years 2012 to 2021. The angle of manufacturing sector was specially considered since these firms make up roughly 10% of Iceland´s GDP (World Bank, 2022) and aim to maximize their production through their tangible assets. With a total of 10,405 usable observations, we narrow the dataset as a whole down into three sub datasets 2012-2021 (99%), 2012-2021 (95%) and 2012-2021 (90%) to prevent possible outliers. This research follows prior published literature that employs a descriptive analysis of the data and then a multivariate linear regression model. The descriptive analysis shows that the Icelandic manufacturing firms are highly leveraged and that roughly 30% of the firms are over leveraged, meaning that they have more total debt than total assets. Literature that considers leverage as an independent variable and firm performance as a dependent variable depicts that four estimations must take place in the following panel data estimations: Ordinary Least Squares, Random Effects, Fixed Effect and the GMM model. This study employs these models and finds that leverage has a statistically significant negative relationship with firm performance variable ROA in all four estimations. Secondly, this study finds that leverage amongst the Icelandic manufacturing firms has a curvilinear relationship with the firm performance measure ROA. Based on the curvilinear relationship found in this study, Icelandic manufacturing firms should aim to have a target debt ratio of no more than 53,6% to maximize their return on total assets. The results in this study are in line with prior empirical literature in this field and the pecking order theory that insists that leverage has a negative relationship with firm performance.